Sexual dimorphism in relationships between of uricemia and some psycho-neuro-endocrine parameters - Popovych, Igor; Gozhenko, Anatoliy; Bombushkar, Igor; Korda, Mykhaylo; Zukow, Walery (Journal of Education, Health and Sport, 2015)
Background. There is a hypothesis that urate is not only the end product of the metabolism of purines like adenosine, but even more a novel target for neuroprotection. The purpose of this study, conducted in line with this hypothesis, is to clarify the relationship between the level of uricemia and EEG/HRV parameters both in men and women. Materials and Methods. The object of observation were almost healthy volunteers: 30 females (30÷76; 49±13 y) and 31 males (24÷69; 47±12 y). In basal conditions we estimated the state of the autonomous regulation by the method HRV, recorded EEG, determined level of uric acid and testosterone as well as estimated level of the trait and reactive anxiety. After 4 or 7 days, repeated testing was performed. Results. The method of canonical correlation analysis revealed a strong urato-neural relationships in both men (R=0,709; R2=0,503; Adjusted R2=0,393) and women (R=0,812; R2=0,659; Adjusted R2=0,542). Moreover, in women, the factor structure of the neural root is almost completely different from that in men, and also includes reactive anxiety and HRV parameters, which are absent in the factor structure of men. In addition, significant differences were found between the profiles of urato-neural correlations of women of reproductive age and postmenopausal women. Conclusion. The level of uricemia is significantly related to a number of parameters of EEG, HRV and anxiety. The strength and even the direction of the correlations are determined by factors linked to gender.